Glutaric Aciduria Type 1: Comparison between Diffusional Kurtosis Imaging and Conventional MR Imaging - Bian, B.; Liu, Z.; Feng, D.; Li, W.; Wang, L.; Li, Y.; Li, D. (American Journal of Neuroradiology, 2023)
BACKGROUND AND PURPOSE: Routine MR imaging has limited use in evaluating the severity of glutaric aciduria type 1. To better understand the mechanisms of brain injury in glutaric aciduria type 1, we explored the value of diffusional kurtosis imaging in detecting microstructural injury of the gray and white matter.MATERIALS AND METHODS: This study included 17 patients with glutaric aciduria type 1 and 17 healthy controls who underwent conventional MR imaging and diffusional kurtosis imaging. The diffusional kurtosis imaging metrics of the gray and white matter were measured. Then, the MR imaging scores and diffusional kurtosis imaging metrics of all ROIs were further correlated with the morbidity scores and Barry-Albright dystonia scores.RESULTS: The MR imaging scores showed no significant relation to the morbidity and Barry-Albright dystonia scores. Compared with healthy controls, patients with glutaric aciduria type 1 showed higher kurtosis values in the basal ganglia, corona radiata, centrum semiovale, and temporal lobe (P < .05). The DTI metrics of the basal ganglia were higher than those of healthy controls (P < .05). The fractional anisotropy value of the temporal lobe and the mean diffusivity values of basal ganglia in glutaric aciduria type 1 were lower than those in the control group (P < .05). The diffusional kurtosis imaging metrics of the temporal lobe and basal ganglia were significantly correlated with the Barry-Albright dystonia scores. The mean kurtosis values of the anterior and posterior putamen and Barry-Albright dystonia scores were most relevant (r = 0.721, 0.730, respectively). The mean kurtosis values of the basal ganglia had the best diagnostic efficiency with area under the curve values of 0.837 for the temporal lobe, and the mean diffusivity values of the basal ganglia in glutaric aciduria type 1 were lower than those in the control group (P < .05). The diffusional kurtosis imaging metrics of the temporal lobe and basal ganglia were significantly correlated with the Barry-Albright dystonia scores. The mean kurtosis values of the anterior and posterior putamen and Barry-Albright dystonia scores were most relevant (r = 0.721, 0.730, respectively). The mean kurtosis values of the basal ganglia had the best diagnostic efficiency with area under the curve values of 0.837.CONCLUSIONS: Diffusional kurtosis imaging provides more comprehensive quantitative information regarding the gray and white matter micropathologic damage in glutaric aciduria type 1 than routine MR imaging scores.ADaxial diffusivityAKaxial kurtosisAPanterior putamenAUCunder the curveBADBarry-Albright dystoniaCBHcerebellar hemisphereCHcaudate headCRcorona radiataCScentrum semiovaleDKIdiffusional kurtosis imagingDNbilateral dentate nucleusFAfractional anisotropyFLfrontal lobesGA-1glutaric aciduria type 1GCDHglutaryl-CoA dehydrogenaseGPglobus pallidusHChealthy controlMDmean diffusivityMKmean kurtosisPponsPLparietal lobesPPposterior putamenRDradial diffusivityRKradial kurtosisROCreceiver operating characteristic curveSNsubstantia nigraThthalamusTLtemporal lobes